Systematic Assessment of the Interoperability Requirements and Challenges of Secure Blockchain-Based Electronic Health Records. (21st July 2022) - Reegu, Faheem Ahmad; Abas, Hafiza; Hakami, Zaid; Tiwari, Sanatan; Akmam, Rudzidatul; Muda, Iskandar; Almashqbeh, Hashem Ali; Jain, Rituraj
Abstract : A peer-to-peer (P2P) decentralized information-sharing network is used to share data and maintain security, privacy, and integrity standards called blockchain. In this case, information sharing and updating require regular simplification. The presented systematic review mainly focuses on the interoperability of electronic health records (EHRs) using blockchain. Correspondingly, 18 blockchain-based solutions were selected to address the interoperability challenges of EHRs. The limitation of solutions includes reliability, privacy, integrity, sharing, and standards. This systematic review contains six phase's research question, research phase, article selection, abstract-based keyword, data extraction, and progress tracking. Various Web resources such as Google Scholar, Web of Science, and IEEE are used to extract the relevant manuscripts. Primarily, 18 articles were selected to present the interoperable requirements of EHRs using blockchain, standards of blockchain-based EHRs, and solutions for interoperability of EHRs using blockchain. The conducted study explains the best available interoperable blockchain-based EHR standards, implementations, applications, and challenges.